DESMIN EXPRESSION AS A MARKER OF CARDIOMYOCYTE CYTOSKELETAL DAMAGE UNDER CARBON MONOXIDE EXPOSURE - Mamedova Guletar Telman kizi; D.A. Khasanova (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Desmin is an intermediate filament protein that maintains the structural integrity of cardiomyocytes and supports the spatial organization of myofibrils. Changes in desmin expression may reflect the severity of cytoskeletal damage in the myocardium under hypoxic-toxic conditions.